Heart of a champion - Deuker, Carl. (Boston : Joy Street Books, 1993)
Seth faces a strain on his friendship with Jimmy, who is both a baseball champion and something of an irresponsible fool, when Jimmy is kicked off the team.
Keywords: Baseball -- Fiction; Friendship -- Fiction